Policy Change and Innovation in Multilevel Governance - Benz, Arthur (Edward Elgar Publishing, 2021)
Multilevel governance divides powers, includes many veto players and requires extensive policy coordination among different jurisdictions. Under these conditions, innovative policies or institutional reforms seem difficult to achieve. However, while multilevel systems establish obstructive barriers to change, they also provide spaces for creative and experimental policies, incentives for learning, and ways to circumvent resistance against change. As the book explains, appropriate patterns of multilevel governance linking diverse policy arenas to a loosely coupled structure are conducive to policy innovation.